On some aspects of decidability of annotated systems - Abe, J. M.; Akama, S.; Arabnia, H. R. (C S R E A Press, 2001)
In this paper, we discuss some results of decidability of annotated systems. The annotated propositional logic Ptau and its S5 type modal extension S5tau are shown to be decidable. These results reveal that annotated systems are computationally attractive as the foundations of paraconsistent reasoning.
Keywords: annotated logics; paraconsistent logics; decidabitity